Corporate social responsibility and branding: a new view to the management strategies - Del Río-Cortina, Jorge Luis; Cardona -Arbeláez, Diego; Guacarí-Villalba, Abel (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Corporate Social Responsibility, CSR, has been studied mainly from a financial performance perspective; hence there is little development around the relationship between CSR and the process of brand building, called Branding. Branding is important as a strategy to generate positive effects in companies. This article makes an approximation to this discussion, providing elements that allow us to understand how from Corporate Social Responsibility can be managed the brand of the companies, so that strategies are generated which positively impact the organization at all levels. The findings suggest that an adequate management of CSR, combined with the correct management of the brand can have an impact on the growth and profitability of companies.